Pengaruh Peran, Kinerja Penyuluh Pertanian dan Lahan terhadap Produksi Padi Desa Cangkringsari - Putri, Nabila Amelia; Soedarto, Teguh; Tondang, Ika Sari (Universitas Galuh, 2025)
The study was quantitative research to analyze the influence of the role performance of agricultural extension and land on rice production with the location in Cangkringsari Village, Sukodono District, Sidoarjo Regency. A simple random sample does the sampling method with the criteria of the farmer's land. The number of sample farmers was 55 people. The study utilized SEM-PLS supported by the SmartPLS 4.0 program. The findings indicated the significance of agricultural extension workers' role obtained a T-statistic value of 2.103 or P-values of 0.018 and a path coefficient value of 0.207, which emphasized that the role of agricultural extension workers had a positive and significant influence on rice production, the performance of agricultural extension workers with a T-statistic value of 3.950 or P-values of 0, 000 and the path coefficient value of 0.518 which emphasizes that the performance of agricultural extension workers has a positive and significant influence on rice production. Land obtained a T-statistic value of 2.176 or P-value of 0.015 and a path coefficient value of 0.262, which means land has a positive and significant influence on rice production.